Attenuation of ferroptosis as a potential therapeutic target for neuropsychiatric manifestations of post-COVID syndrome - Sousa, Ricardo A. L.; Yehia, Asmaa; Abulseoud, Osama A. (Frontiers in Neuroscience, 2023)
Coronavirus disease-19 (COVID-19), caused by severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2), is associated with the persistence of pre-existing or the emergence of new neurological and psychiatric manifestations as a part of a multi-system affection known collectively as “post-COVID syndrome.” Cognitive decline is the most prominent feature among these manifestations. The underlying neurobiological mechanisms remain under intense investigation. Ferroptosis is a form of cell death that results from the excessive accumulation of intracellular reactive iron, which mediates lipid peroxidation. The accumulation of lipid-based reactive oxygen species (ROS) and the impairment of glutathione peroxidase 4 (GPX4) activity trigger ferroptosis. The COVID-19-associated cytokine storm enhances the levels of circulating pro-inflammatory cytokines and causes immune-cell hyper-activation that is tightly linked to iron dysregulation. Severe COVID-19 presents with iron overload as one of the main features of its pathogenesis. Iron overload promotes a state of inflammation and immune dysfunction. This is well demonstrated by the strong association between COVID-19 severity and high levels of ferritin, which is a well-known inflammatory and iron overload biomarker. The dysregulation of iron, the high levels of lipid peroxidation biomarkers, and the inactivation of GPX4 in COVID-19 patients make a strong case for ferroptosis as a potential mechanism behind post-COVID neuropsychiatric deficits. Therefore, here we review the characteristics of iron and the attenuation of ferroptosis as a potential therapeutic target for neuropsychiatric post-COVID syndrome.